THE ILLOCUTIONARY LEVEL OF “SPEECH ACTS” THEORY: A STYLISTIC ANALYSIS OF RICHARD MATHESON’S “BUTTON, BUTTON” - Husnat Ahmed Tabassam, Shah Faisalullah , Hafsa Yasin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The objective of the study is to analyze the speech acts, performed by the characters in short story ‘Button, Button’ on the illocutionary level of speech acts theory by John Austin (1962). The author believed that two major types of utterances exist; one is constative, used to illustrate the scenario, and the other is performative that illustrates a speech act. Speech acts are further classified into locutionary, illocutionary and perlocutionary acts. Linguistic expressions have virtual meanings which contribute in truth conditions of sentences. It gives linguistic meaning in the recital of speech acts in terms of consumption of words and sentences. Analysis indicates classification of speech acts at delivery level, direct and indirect at structural level. Illocutionary level can be declarative, representative, expressive and commissive. There are numerous functions of speech acts we i.e. uniqueness, social depiction, personal grooming, communal grooming and pleasure (Flor, 2010). The current study adopted qualitative research method which is kept under consideration during data analysis.